2015
DOI: 10.1080/10408398.2015.1060190
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid: A potent fatty acid linked to animal and human health

Abstract: Conjugated linoleic acid (CLA) is a mixture of isomers of linoleic acid (C18:2 n-6), which is mostly found in the ruminant meat and dairy products. The CLA is known to have many potential health benefits, and considered a potent powerful fatty acid, which is linked to animal and human health. The present work aims to discuss the source and production, mechanism of action, and effects of CLA on humans, poultry, and ruminants by reviewing the recent studies carried out on CLA. Despite most of the recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 112 publications
(122 reference statements)
1
49
0
Order By: Relevance
“…We have observed a positive association between CLA% and blood pressure, in contrast to studies suggesting that CLA supplementation may decrease blood pressure . However, CLA% was associated with lower levels of CRP, consistent with clinical and dietary intervention studies suggesting an anti‐inflammatory effect of CLA . Other studies, however, have reported no association or positive associations between CLA and inflammation .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We have observed a positive association between CLA% and blood pressure, in contrast to studies suggesting that CLA supplementation may decrease blood pressure . However, CLA% was associated with lower levels of CRP, consistent with clinical and dietary intervention studies suggesting an anti‐inflammatory effect of CLA . Other studies, however, have reported no association or positive associations between CLA and inflammation .…”
Section: Discussionsupporting
confidence: 75%
“…CLA is produced naturally in ruminant animals, such as cows, sheep, and goats. Dairy products are a primary source of cis ‐9, trans ‐11‐CLA (c9,t11‐CLA), the most prevalent CLA isomer, in the diet of humans . Epidemiological studies have shown a strong positive association between the intake of TFAs and coronary heart disease (CHD) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Animal and, to a lesser extent, human studies have shown promising results for CLA supplementation in the prevention of atherosclerotic plaque development and improvements in lipid profile [147], [148]. There have also been several studies suggesting that CLA supplementation in humans can favourably alter body composition, by reducing body fat percentage [149], [150], [151], however, other studies have not observed this [152], [153].…”
Section: ‘Browning’ Cardiac and Vascular Adipose Tissues To Reduce Camentioning
confidence: 99%